LEARNING MODEL BASED ON CREATIVITY DEVELOPMENT IN IMPROVING LITERATURE APPRECIATION ABILITY (MODEL PEMBELAJARAN BERBASIS PENGEMBANGAN KREATIVITAS DALAM MENINGKATKAN KEMAMPUAN APRESIASI SASTRA) - Bambang Eko Hari Cahyono; Indrya Mulyaningsih (Universitas PGRI Sumatera Barat, 2022)
Learning literature in universities has not been able to increase creativity even though many models have been used. Therefore, this study aims to describe the effectiveness of the learning model based on creativity development in improving students' literary appreciation abilities. This quasi-experimental research uses a Quasi-experimental Design model of the Non-Equivalent Before-after Design. The population includes students of the Indonesian Language Education Study Program at the University of PGRI Madiun and STKIP PGRI Pacitan. Sample selection was done randomly. Data were collected through a short story appreciation ability test. Data analysis was carried out in two stages, namely the analysis prerequisite test stage and the data analysis stage. Data analysis used independent t-test. Based on the results of data analysis and discussion, it can be concluded that the learning model based on creativity development can improve students' ability to appreciate short stories. This enhancement has proven to be very effective. However, the application of this learning model needs to be supported by the environment, facilities, and curriculum.